Harmonic mappings in the plane - Duren, Peter L., 1935- (Cambridge tracts in mathematics, 2004)
This first comprehensive account of the theory of planar harmonic mappings, meant for non-specialists, treats both the generalizations of univalent analytic functions and the connections with minimal surfaces. Included are background material in complex analysis and a full development of the classical theory of minimal surfaces, including the Weierstrass-Enneper representation.